PENGGUNAAN KARYA SASTRA DALAM PENGAJARAN MEMBACA SEBAGAI SARANA MENINGKATKAN MINAT BACA - Idha Nurhamidah (Dinamika Bahasa dan Budaya, 2016)
This study tried to re-examine the the significant role of literature as readingmaterials in class, and the appropriateness of involving students in teaching andlearning process in which they were supposed to provide reading materials forclass discussions. With the text provided by the students, hopefully they would beencouraged to read; thereby increasing their reading interests. However, the twocycleaction research revealed that such learning and teaching processes did notcontribute to improving their reading preferences. Interestingly the seemingly lessinterests in reading did not have any effects on their reading scores. There weresignificant increases in the pre-test and the post-test, indicating that the studentsstill managed to read the texts for good scores. It is therefore recommended thatthe use of authentic texts in line with the students’ major be still preferable.